O corpo-outro: discursos e sentidos de estudantes de graduação da Universidade Federal de Sergipe - Correia, Eanes dos Santos (2022)
The university is much more than its walls. Students are more than people who study. They are stories, experiences, lives that intersect, subjects who think, act, say things, relate to each other and the world. They are bodies that move, speak without neutrality. These bodies have desire, discourse that gives meaning and are challenged by a culture that constitutes them inside and outside educational institutions. The purpose of this research is to analyze the discourses and meanings that are produced about the body by undergraduate students at the Federal University of Sergipe, Brazil, in accordance to the theoretical reference and having the methodological support of French Discourse Analysis under the perspective of Eni Orlandi.The analysis is based on the following question: “what discourses and meanings are produced about the body by undergraduate students at the Federal University of Sergipe?”. This text is a qualitative research, which aims to analyze the data regarding the senses and discourses. As theoretical contributions, it was used references from Jacques Lacan, David Le Breton and Vygotsky whose researches have in common the body and the spectrums it reaches.The instruments used to collect data production included questionnaire, knowledge inventory, free word association and semi-structured interview. The research population is made up of students from undergraduate centers: Center for Applied Agricultural Sciences (CCAA); Center for Biological and Health Sciences (CCBS); Center for Exact Sciences and Technology (CCET); Center for Applied Social Sciences (CCSA); and Education and Human Sciences Center (CECH) and are current students at the Federal University of Sergipe, on the São Cristóvão campus. This research shows the implication of the Other in the speeches of students at the Federal University of Sergipe regarding the body. The discourses produced were: Conceptual Discourse, Punctual Discourse, Functional Discourse, Discourse on Place/Situation of Knowledge and Intellectual Discourse. In this way, it is concluded that the speeches and meanings produced to the body by the students are questioned by the institution of the Other – of Education. The conclusion culminated in the elaboration of the Mathema of Body, given by the expression Body-Other: speech + desire + sense + Other. Finally, it is concluded that the body is spoken by the voice of the Other by which is recognized, the body is the Other, Body-Other.